Analisis Penerapan PSAK 224 pada Grup LIPPO yang Terdaftar di Bursa Efek Indonesia - Idawati, Wiwi; Verdianto, Keevin Keane; Sihotang, Celine D. A. P.; Liem, Cherry (Journal of Business And Entrepreneurship, 2025)
A lot of companies in Indonesia have ownership structures controlled by families or groups, increasing the potential for transactions with related parties. This can potentially lead to the risk of conflicts of interest and manipulation of financial data. To address these risks, the Financial Accounting Standards Board of the Indonesian Institute of Accountants (DSAK IAI) established Statement of Financial Accounting Standards (PSAK) Number 224 concerning Related Party Disclosures. This study was conducted to identify the compliance of the disclosure of key management compensation and transactions with related parties during the 2019-2023 period with PSAK 224. The subjects of this research are Lippo Group companies listed. This research uses a qualitative descriptive method, by analyzing the data contained in the annual report. The results showed that in the 2019-2023 period, the disclosure of key management compensation by Lippo Group companies still did not cover all components completely, except for short-term employee benefits. Meanwhile, the disclosure of transactions with related parties could not be declared complete in accordance with paragraph 18 of PSAK 224.